HOUT-09. DEVELOPING OMMAYA CLINICS FOR LEPTOMENINGEAL CARCINOMATOSIS (LMC): STANDARDIZED TREATMENT, IMPACT ON SURVIVAL/NEUROLOGIC DISABILITY AND ROLE FOR ADVANCED PRACTITIONERS. (11th November 2019) - Leese, Erika; Manikowski, Jesse; Mahadevan, Anand; Conger, Andrew; Mongelluzzo, Gino; Tosha Gatson, Na
Abstract: Leptomeningeal carcinomatosis (LMC), first described in 1870, involves leptomeningeal and CSF invasion by neoplastic cells and portends poor survival. Among solid tumor LMC, breast cancer is the most common followed by lung and melanoma. With an estimated 100, 000+ new cases yearly, the dual-edged sword of systemic treatment drives the increasing incidence as cancer patients live longer and on non-CNS penetrating therapies. Addition of immuno-oncotherapies has impacted LMC survival. At time of diagnosis, most patients have multiple neurologic disabilities. Multiple reports on the topic have not yielded consistent treatment standards to extend patient survival. Most agree that local CNS control coupled with systemic therapy offers the best survival. Still, there are few established Ommaya clinics (OC). Importantly, LMC is a common exclusionary criterion for clinical trials. A single institutional evaluation of 147 patients (2012–2019) with a diagnosis of LMC was completed. 69 of 147 were excluded, leaving 48 pre-OC and 30 OC patients. The mOS (weeks) of those treated with intrathecal chemotherapy (ITC) versus no ITC was compared between cohorts: pre-OC and OC (3.36, 15.29****). Average KPS at time of diagnosis in pre-OC and OC was 70–80 (ECOG 2–3). The mOS was compared between breast (5, 28*), lung (3, 3) and melanoma (5, 10*) in the pre-OC and OC respectively. The treatment standardized for the OC includes whole-brain radiation, Ommaya reservoir placement, systemic treatment, treatment with ITC (2x weekly – q other month) and MR imaging every 3 months. Breast cancer patients fared the best followed by melanoma and lung patients in the OC. With use of advanced practitioners (APs), standardization of treatment and surveillance is achievable. Patients treated according to a standardized OC regimen experienced longer overall survival along with a 10% improvement in KPS after two months of treatment. Development of institutional OCs reduces treatment variability and increases clinical surveillance.